Study of surface bonding imperfection effects on equivalent identified dynamic Young's and shear moduli using a modal based joint identification method. (February 2015) - Meshki, M.M.; Nobari, A.S.; Nikbin, K.
Abstract: In this paper the effects of defects on the equivalent identified dynamic Young's and shear moduli of flexible structural adhesive joints have been investigated. Adhesive joints were subjected to initial surface bonding imperfection, in order to simulate the defects. Several debond patterns have been applied artificially on single-lap joint specimens and joint identification process has been performed for both bending and shear modes to see how surface bonding imperfection can affect equivalent identified dynamic Young's and shear moduli of the adhesive. Using a direct modal based method to identify mechanical characteristics of joints has been shown that degradation of the equivalent moduli of debonded joint is correlated to both frequency and mode shapes. The results reveal that debonding is easily detectable in bending modes whereas degradation in shear modes is also correlated to debonding orientation and mode shapes. Three identical specimens have been tested for each case to prove the consistency of the results. Highlights: This paper analyses the fault effect on the mechanical properties of structural adhesive. Dynamic characteristics of adhesive for healthy and faulty cases were identified. Adhesive debonding failure as small as 5% of bonding area was successfully detected.